Beyond Birth and Death: A Clarion Call to Action on Nepal's Demographic Transition - Adhikari, Keshab Prasad (Nepal Journal of Sociology, 2024)
By probing the available literature and models on demographic transitions and population dividends, this essay maps the compelling evolution of population dynamics. Existing models and literature highlight how socioeconomic conditions and biological factors have shaped the realities of demographic shifts. On the one hand, individuals and communities from different societies strive to enhance their living standards through foreign employment, leading to youth migration. On the other hand, they experience alarming changes in mortality and fertility rates, significantly altering the demographic structure. These everyday occurrences have created a “demographic window of opportunity” within the global context of demographic shifts and population dividends, compounded by the prevailing socio-cultural forces of migration and globalization. Although this trend aligns with global patterns, Nepal faces the daunting task of managing both youth migration and an ageing population. Despite their significance, these shifts and trends have been less prominent in the discourses and dialogues initiated by sociologists, economists, and demographers.